2008
DOI: 10.1177/0091552108319604
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social and Cultural Capital on Student Persistence

Abstract: This study examines the influences of social and cultural capital on persistence from 1st to 2nd year and how these effects differ between community colleges and 4-year institutions. Results show that social and cultural capital have a positive association with student persistence overall but matter less when students begin at a community college.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 36 publications
1
92
1
1
Order By: Relevance
“…Another study employed the use of social capital to demonstrate that parental expectations, parental involvement, and peer influence are manifest in decisions that affect college degree aspirations of both males and female students; however, the effects differed by gender with the effects of social capital appearing to be more prominent in females than in males (Wells et al, 2011) It becomes clear that a student's social capital is highly important in their decision-making about and aspirations in higher education, and high levels of social capital are likely to have a positive influence on college student decision-making and aspiration. The effects of social capital, such as the awareness of educational expectations and insight into the college-going experience, will continue well into the first years of attending a college or university (Wells, 2008).…”
Section: Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study employed the use of social capital to demonstrate that parental expectations, parental involvement, and peer influence are manifest in decisions that affect college degree aspirations of both males and female students; however, the effects differed by gender with the effects of social capital appearing to be more prominent in females than in males (Wells et al, 2011) It becomes clear that a student's social capital is highly important in their decision-making about and aspirations in higher education, and high levels of social capital are likely to have a positive influence on college student decision-making and aspiration. The effects of social capital, such as the awareness of educational expectations and insight into the college-going experience, will continue well into the first years of attending a college or university (Wells, 2008).…”
Section: Social Capitalmentioning
confidence: 99%
“…These results were consistent with what is presented in the literature about social capital within the family. For example, Wells (2008) demonstrated that parental involvement is a factor in a student's decision to enroll in a two-year college, a four-year college, or to not enroll in college at all. In addition, Wells et al (2011) linked parental expectations and parental involvement to the postsecondary educational expectations for both male and female high school students.…”
Section: Reported Thatmentioning
confidence: 99%
“…However, diverse college students bring numerous resources to the college experience derived from their social and cultural contexts that can be leveraged to support collegiate academic success (Barbatis, 2010;Wells, 2008). These cultural and social resources in terms of linguistic resources, parental involvement, aspirational and achievement focus to name a few are powerful success resources for students from diverse backgrounds Yosso, 2005).…”
Section: Social and Cultural Capitalmentioning
confidence: 99%
“…These cultural and social resources in terms of linguistic resources, parental involvement, aspirational and achievement focus to name a few are powerful success resources for students from diverse backgrounds Yosso, 2005). Social capital can also provide diverse college students with resources that can help them overcome significant obstacles to college completion (Hallet, 2013;Wells, 2008;Yosso, 2005).…”
Section: Social and Cultural Capitalmentioning
confidence: 99%
See 1 more Smart Citation